Successful clinical management of chronic mastitis cum udder abscess in a transition cow - M, Venkatesan; G, Devadharshini; K, Rajeshwari; K, Jayalakshmi; A, Thangavelu; D, Sumathi (Indian Journal of Veterinary Medicine, 2024)
Based on ultrasonographic findings and ABST results, a Holstein Friesian cross-bred cow, which had previously experienced udder swelling accompanied by thick yellowish milk discharge from all quarters except the left fore quarter, characterized by curdy yellowish discharge, was diagnosed and subsequently treated for chronic mastitis cum udder abscess.